From Passive to Proactive: Transforming Geography Education through Problem-Based Learning to Foster Critical Thought - Fauziah, Siti Alfiany; Aini, Zubaidah Nur; Zahra, Berliana Siti; Agessi, Yumna Afanin Putri (Future Space: Studies in Geo-Education, 2024)
The appropriate use of interactive multimedia is one way to increase the effectiveness of the learning process. The integration of the Google Sites platform as an interactive multimedia tool within the guided inquiry learning model aims to enhance students' critical thinking in solving environmental issues. Educational content provided through the Google Sites platform facilitates student exploration of endogenous and exogenous energy issues and their impacts on life. The purpose of this study was to determine the effect of guided inquiry model assisted by Google Sites on critical thinking skills in geography subjects. This research was conducted at Islamic Senior High School Kepanjen 1 using post-test only control group design with experimental class 10-4 and control class 10-1. Data collection in this study used critical thinking post-test that has been tested for validity and reliability. The hypothesis testing using an independent sample t-test yielded a Sig. (2-tailed) value of 0.004, indicating statistical significance (p < 0.05). The mean critical thinking score in the experimental class was significantly higher than in the control class, leading to the rejection of H0 and acceptance of H1. This suggests that the guided inquiry model assisted by Google Sites positively impacts students' critical thinking skills. The application of the guided inquiry model assisted by Google Sites actually emphasises students to continue to collaborate in finding solutions to problems and support the critical thinking skills of students in geography subjects.